Kidney Health Plan 2033 in Korea: bridging the gap between the present and the future - Do Hyoung Kim; Young Youl Hyun; Jin Joo Cha; Sua Lee; Hyun Kyung Lee; Jong Wook Choi; Su-Hyun Kim; Sang Youb Han; Cheol Whee Park; Eun Young Lee; Dae Ryong Cha; Sung Gyun Kim; et al. (The Korean Society of Nephrology, 2024)
In response to the increase in the prevalence of chronic kidney disease (CKD) in Korea, the growth of patients requiring renal replacement therapy and the subsequent increase in medical costs, the rapid expansion of patients with end-stage kidney disease (ESKD), and the decrease in patients receiving home therapy, including peritoneal dialysis, the Korean Society of Nephrology has proclaimed the new policy, Kidney Health Plan 2033 (KHP 2033). KHP 2033 would serve as a milestone to bridge the current issues to a future solution by directing the prevention and progression of CKD and ESKD, particularly diabetic kidney disease, and increasing the proportion of home therapy, thereby reducing the socioeconomic burden of kidney disease and improving the quality of life. Here, we provide the background for the necessity of KHP 2033, as well as the contents of KHP 2033, and enlighten the Korean Society of Nephrology's future goals. Together with patients, healthcare providers, academic societies, and national policymakers, we need to move forward with goal-oriented drive and leadership to achieve these goals.